Propagation characteristics of Gaussian beams in plasma sheath turbulence. Issue 2 (1st January 2017) - Li, Jiangting; Yang, Shaofei; Guo, Lixin
Abstract : In this study, the new fractal model and power spectrum of plasma sheath turbulence are established based on the fractal dimensions in hypersonic turbulence that were measured through experiments. The expression for beam spot size, scintillation index, angle‐of‐arrival fluctuation, and beam wander are obtained from the power spectrum. Finally, the propagation characteristics of a Gaussian beam in a turbulent plasma sheath are simulated. The authors' results indicate that plasma sheath turbulence can lead to amplitude and phase variations. A larger variance in the plasma sheath turbulence causes a more evident refractive index fluctuation and a greater effect on the Gaussian beam propagation characteristics. On the contrary, a larger Reynolds number reduces the effect of the plasma sheath turbulence on the Gaussian beam. This new power spectral model is fundamental to understanding Gaussian beam propagation in plasma sheath turbulence and may provide a reference for the imaging and communication system under the effect of plasma sheath turbulence.